Hydraulic efficiency of grate and curb inlets for urban storm drainage - Comport, Brendan, author; Thornton, Christopher, advisor; Kampf, Stephanie, committee member; Roesner, Larry, committee member (Colorado State University. Libraries, 2010)
Stormwater runoff from an urban landscape is typically conveyed through networks comprised of streets, gutters, inlets, storm sewer pipes, and treatment facilities. Objectives of this research program included evaluating the hydraulic efficiency of three storm-drain inlet types and developing design methodology. Denver Type 13 and 16 grate inlets and Colorado Department of Transportation Type R curb inlet were evaluated during the course of testing. Grate inlets were tested in a grate-only and combination inlet configuration. A one-third Froude scale model was constructed to permit testing longitudinal slopes from 0.5 to 4 %, cross slopes from 1 to 2 %, prototype depths from 0.333 to 1 ft, and prototype inlet lengths from 3.3 to 15 ft. A total of 318 tests were performed for the various configurations. Inlets tested are currently used by the Urban Drainage and Flood Control District (UDFCD), and have never been tested or studied in a manner such that an efficiency relationship is known. Efficiency is defined in this study as the percentage of total street flow removed by an inlet design. Current design practices are typically based upon “Hydraulic Engineering Circular 22” (HEC 22), which addresses the use of other inlet types, but it does not provide guidance specific to the three inlets tested. Need for this study arose from general uncertainty in matching inlets used by the UDFCD to methods presented in HEC 22. This uncertainty in design relates to sizing inlets and in determining the level of flood protection afforded by their use. After examining the collected test data, dimensional analysis was conducted on influencing variables and regression techniques were used to develop new equations for prediction of inlet efficiency. In addition, HEC 22 methods were modified to include the three inlets tested. Street flow was observed to be often supercritical and non-uniform, with efficiency highly dependent upon flow velocity and inlet length. For a given inlet length, the combination inlets were found to perform most efficiently. Inlet efficiencies computed from the developed empirical equations and modified HEC 22 methods were compared to the collected test data and current HEC 22 methods. When compared to prototype data for typical design flow depths of 0.5 to 1 ft, the empirical equations showed accuracy to within 9% efficiency error for the combination inlets which is a 30% improvement over current HEC 22 methods. All methods for the type R inlet showed similar results at 0.5 and 1 ft depths, with differences up to 15 % occurring at the lowest depth of 0.333 ft. Furthermore, details of the testing and analysis were presented and suggestions for further research were made.
Covers not scanned.
Keywords: Road drainage; Storm sewers; Urban runoff